Comparison of three dielectric barrier discharges regarding their physical characteristics and influence on the adhesion properties on maple, high density fiberboards and wood plastic composite. (3rd November 2017) - Peters, F; Hünnekens, B; Wieneke, S; Militz, H; Ohms, G; Viöl, W
Abstract: In this study, three different dielectric barrier discharges, based on the same setup and run with the same power supply, are characterized by emission spectroscopy with regards to the reduced electrical field strength, and the rotational, vibrational and electron temperature. To compare discharges common for the treatment on wood, a coplanar surface barrier discharge, a direct dielectric barrier discharge and a jet system/remote plasma are chosen. To minimize influences due to the setups or power, the discharges are realized with the same electrodes and power supply and normalized to the same power. To evaluate the efficiency of the different discharges and the influence on treated materials, the surface free energy is determined on a maple wood, high density fiberboard and wood plastic composite. The influence is measured depending on the treatment time, with the highest impact in the time of 5 s.